Spherically Symmetric Solutions for a Coupled Compressible Navier-Stokes/Allen-Cahn System (Journal of Partial Differential Equations, 2020)
In this paper, we consider the initial boundary value problem of a coupledcompressible Navier-Stokes/Allen-Cahn system which is described the motion of amixture of two viscous compressible fluids in 3D. Our aim is to show the existence anduniqueness of local classical solution under the assumption of spherically symmetriccondition for initial data ρ0 without vacuum state.
Keywords: Navier-Stokes equations; Allen-Cahn equation; local solutions; spherically symmetry.